2018
DOI: 10.1210/jc.2018-01221
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal and Metabolic Effects of Coenzyme Q10 and/or Vitamin E in Patients with Polycystic Ovary Syndrome

Abstract: In conclusion, CoQ10 with or without vitamin E supplementation among women with PCOS had beneficial effects on serum FBS and insulin levels as well as HOMA-IR and total testosterone levels. However only co-supplementation was able to affect SHBG concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 44 publications
0
52
0
1
Order By: Relevance
“…Similar results were reported in a few more randomized clinical trials, although with higher vitamin D dose [44] , [45] . Vitamin E was shown to have beneficial effects on the metabolic and clinical signs of PCOS, alone or in combination with coenzyme Q10 and omega-3 fatty acids [46] [49] . Two physicians reported advising the use of herbal supplements ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported in a few more randomized clinical trials, although with higher vitamin D dose [44] , [45] . Vitamin E was shown to have beneficial effects on the metabolic and clinical signs of PCOS, alone or in combination with coenzyme Q10 and omega-3 fatty acids [46] [49] . Two physicians reported advising the use of herbal supplements ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that CoQ10 with or without vitamin E supplementation for 8 weeks among patients with PCOS significantly decreased serum total testosterone levels (P < 0.001) compared with those of the placebo group. CoQ10 supplementation in combination with vitamin E significantly improved sex hormone-binding globulin (SHBG) levels compared with other groups (P = 0.008) [74].…”
Section: Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 99%
“…TT was measured in 13 studies [25][26][27][28][29]32,33,[38][39][40]42,43,45]. TMA showed that except for vitamin D, the following nutritional agents were significantly different compared with PA: CoQ10 (MD À0.55, 95%CI À0.68 to À0.43, p < .00001, I 2 ¼ 62),vitamin E (MD À0.61, 95%CI À0.70 to À0.53, p < .0001, inositols (MD 0.55, 95%CI 0.34 to 0.77, p < .00001, I 2 ¼62).…”
Section: Improvement Of Hyperandrogenemiamentioning
confidence: 99%